American Yoga: The Shaping of Modern Body Culture in the United States - Schrank, Sarah (American Studies, 2014)
AMERICAN VEDA: from Emerson and the Beatles to Yoga and Meditation - How Indian Spirituality Changed the West. By Philip Goldberg. THE GREAT OOM: The Improbably Birth of Yoga in America. By Robert Love. HELL-BENT: Obsession, Pain, and the Search for Something Like Transcendence in Competitive Yoga. By Benjamin Lorr. THE SCIENCE OF YOGA: The Risks and Rewards. By William J. Broad. THE SUBTLE BODY: The Story of Yoga in America. By Stefanie Syman. THEOS BERNARD, THE WHITE LAMA. Tibet, Yoga, and American Religious Life. By Paul G. Hackett. YOGA BODY: The Origins of Modern Posture Practice. By Mark Singleton.